Monte Carlo simulation of the BEGe detector response function for in vivo measurements of super(241)Am in the skull - Fantinova, K; Fojtik, P (Radiation physics and chemistry (Oxford, England : 1993), 2014)
This paper reports on the procedure of the BEGe detector characterization for the Monte Carlo calibrations. A project is under way to improve the counting and operating capabilities of the Whole Body Counter (WBC) installed in SURO, v.v.i. (NRPI) Prague, Czech Republic. Possible emergency monitoring should mainly benefit from the rapid, safe and flexible operation of the WBC. The system of the WBC for the detection of low energy X and gamma radiation comprises four HPGe detectors intended for the routine, emergency, and research measurements of persons internally contaminated with low-energy photon emitters, mainly actinides. Among them, super(241)Am is the main subject of interest. A precise detection efficiency calibration of the detector is required for the measurement of activity in individual organs and tissues. The use of physical phantoms in the calibrations is often supplemented with the application of voxel phantoms and a Monte Carlo technique that are used for the calculation of the detector response function and the full energy peak efficiency. Both experimental and computational approaches have been used for the calibration of the BEGe (Broad Energy Germanium) detector. In this paper, the process of the Monte Carlo simulation of the detector response function and the peak efficiency calculation is described. Results of the simulations are provided in the paper and discussed.